Implementation of Human Resources Management at Autism Café Project Malaysia to Improve the Performance of Student With Autism - Sarwani, Sarwani; Subarto, Subarto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Autism is a developmental disorder that affects communication ability, social interaction, and behavior. The Autism Café Project Malaysia is a social initiative aimed at empowering individuals with autism through training and employment opportunities. Effective Human Resource Management (HRM) is crucial to enhancing the performance of autistic students in the workplace. This initiative aims to implement HRM at the Autism Café Project Malaysia to improve the performance of autistic students. Additionally, it aims to provide practical experience for students and faculty in applying HRM concepts in real-world contexts. The activity took place at Sultan Salahuddin Abdul Aziz Shah Polytechnic, Selangor, Malaysia, involving 80 participants including autistic students, students, and faculty members. Methods included preparation, training implementation, practice and simulation, as well as evaluation and monitoring. Training covered personal and social skills development, HRM application, job skills, and entrepreneurship. Through this initiative, autistic students demonstrated improved performance in various tasks at the Autism Café Project. Students gained a better understanding of applying HRM in real situations, while faculty successfully guided and provided constructive feedback. This activity also fostered a more inclusive and supportive community.